On the Optimality of Joint Taxation with Household Production - Henrik Jacobsen Kleven; Claus Thustrup Kreiner (Center for Economic Studies and ifo Institute (CESifo), 2001)
The existing literature suggests that the concern for economic efficiency calls for individual taxation of married couples with a higher rate on the primary earner. This paper reconsiders the choice of tax unit in the Becker model of household production, which includes previous analyses as special cases. In the general framework, where all utility yielding commodities are produced through a combinatiion of market goods and household time, optimal taxation requires joint taxation of the family. This result assumes that there are no restrictions in the use of commodity taxes. In the presence of such restrictions individual taxation is typically optimal. However, this may call for a lower rate on primary earners, unlike the standard result.
Keywords: 330; optimal taxation; household production; time allocation